Using a Cross-Sectional Analysis of Age-Related Variations in Anthropometric Indices and their Association with Cardiometabolic Health in Adult Men - Nawfal, Kanaan Ibrahim; Tiwari, Sandhya; Tiwari, Sandeep; Haq, Mir Ahsan Ul (Physical Education Theory and Methodology, 2024)
Background. Age-related changes in anthropometric indices and their association with cardiometabolic health markers are crucial for understanding health risks in adult men. Objectives. The study aimed to assess age-related variations in anthropometric indices and their correlation with health markers, highlighting potential cardiometabolic health risks in adult men. Materials and methods. A total of 200 men, aged 26 to 50 years, from Delhi-National Capital Region (NCR), India, were sampled using a multistage random sampling technique and divided into 5 age groups, each including 40 individuals. This study examined variations in body measurements such as the hip circumference (HC), waist circumference (WC), body mass index (BMI), and neck circumference (NC) across different age groups, as well as their relationship to health markers like HbA1c and lipid profile. Anthropometric measurements were taken in a standardized environment, and blood samples were taken under fasting conditions for lipid profile and HbA1c measurement. With SPSS software, descriptive statistics, a one-way ANOVA, and the Pearson correlation coefficients were used to analyze the data. Results. Significant age-related differences were found in NC and WC, with NC increasing from 39.61 ± 2.53 cm to 41.20 ± 2.63 cm and WC rising from 89.68 ± 12.08 cm to 98.80 ± 9.90 cm, indicating a trend toward central obesity. BMI and HC showed no considerable variation across age groups. A one-way ANOVA revealed significant differences in NC (F = 3.586, p = 0.008) and WC (F = 6.020, p = 0.005). Pearson’s correlations indicated that NC, BMI, and WC were positively correlated with triglycerides, LDL, and VLDL levels (p < 0.05), while no notable correlations were observed for HbA1c. Conclusions. The study underscores the existence of significant age-related increases in NC and WC, suggesting heightened risks of abdominal obesity and cardiometabolic health issues in older men. Monitoring these anthropometric indices is vital for the early detection of health risks in adult males.